2013
DOI: 10.1002/ece3.439
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite and mtDNA analysis of lake trout, Salvelinus namaycush, from Great Bear Lake, Northwest Territories: impacts of historical and contemporary evolutionary forces on Arctic ecosystems

Abstract: Resolving the genetic population structure of species inhabiting pristine, high latitude ecosystems can provide novel insights into the post-glacial, evolutionary processes shaping the distribution of contemporary genetic variation. In this study, we assayed genetic variation in lake trout (Salvelinus namaycush) from Great Bear Lake (GBL), NT and one population outside of this lake (Sandy Lake, NT) at 11 microsatellite loci and the mtDNA control region (d-loop). Overall, population subdivision was low, but sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 125 publications
(224 reference statements)
2
12
0
Order By: Relevance
“…The first by Northrup, Connor & Taylor () estimated F ST values among lake trout populations from a broad geographic area spanning the Yukon, British Columbia and the North West Territories and found that values ranged from 0.014 for two connected lakes of the same catchment to 0.616 for two lakes located in different catchments (separated by 780 km) that probably belong to different glacial lineages. The second study found no structure among lake trout collected from different basins within one of the largest freshwater ecosystems in Canada, the Great Bear Lake in the North West Territories (Harris et al ., ). Population structure could not be identified despite very large distances separating sampling locations within the lake.…”
Section: Discussionmentioning
confidence: 97%
“…The first by Northrup, Connor & Taylor () estimated F ST values among lake trout populations from a broad geographic area spanning the Yukon, British Columbia and the North West Territories and found that values ranged from 0.014 for two connected lakes of the same catchment to 0.616 for two lakes located in different catchments (separated by 780 km) that probably belong to different glacial lineages. The second study found no structure among lake trout collected from different basins within one of the largest freshwater ecosystems in Canada, the Great Bear Lake in the North West Territories (Harris et al ., ). Population structure could not be identified despite very large distances separating sampling locations within the lake.…”
Section: Discussionmentioning
confidence: 97%
“…MtDNA data collection methods are described in Harris et al (2013). Briefly, the left domain of the control region (d-loop) was amplified with primers tPro2 (Brunner et al, 2001) and ARCH1 (Alekseyev et al, 2009).…”
Section: Molecular Methodsmentioning
confidence: 99%
“…We performed STRUCTURE analyses for two data sets: (1) one consisting of all samples; and (2) one containing only the GBL samples. Given the limited genetic structure that has previously been resolved among Lake Trout from GBL (Harris et al, 2013), we used the LOCPRIOR option in STRUCTURE for the latter analysis to enhance the likelihood of detecting existent population structure in this system (detailed by Hubisz et al, 2009). To avoid biasing the analysis toward the clustering by morph or arm, LOCPRIOR information was included at the sample level (that is, including 13 distinct entities in our LOCPRIOR information and the 13 localities represent various positions within arms).…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…If connectivity is not restricted and gene flow between populations is pervasive, then differentiation should be relatively low (Als et al 2011;Harris et al 2013). Furthermore, when absolute barriers to gene flow are absent, and if populations are in a state of migration-drift equilibrium (Hutchison and Templeton 1999), noticeable patterns of isolation-by-distance (IBD; Wright 1943) should be apparent in stream-dwelling and anadromous salmonids (e.g., Koizumi et al 2006a;Primmer et al 2006).…”
Section: Introductionmentioning
confidence: 99%